THE COMPARATIVE ANALYSIS OF INTERNET DISCOURSE IN UZBEK, RUSSIAN AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2024)
This study examines the subtleties of online conversation in Uzbek, Russian, and English, three different linguistic groups. The objective of this research is to provide light on the similarities and contrasts in the ways that people use different languages to engage in discourse on the internet by conducting a thorough analysis of online communication patterns, linguistic characteristics, and cultural influences. This study uses a mixed-methods approach to investigate the underlying dynamics influencing online conversation within each linguistic group. It does this by combining quantitative linguistic analysis with qualitative content analysis. The results of this study shed light on how language shapes online interactions and further our knowledge of cross-cultural communication in the digital era. This study examines the subtleties of online conversation in Uzbek, Russian, and English, three different linguistic groups. The objective of this research is to provide light on the similarities and contrasts in the ways that people use different languages to engage in discourse on the internet by conducting a thorough analysis of online communication patterns, linguistic characteristics, and cultural influences. This study uses a mixed-methods approach to investigate the underlying dynamics influencing online conversation within each linguistic group. It does this by combining quantitative linguistic analysis with qualitative content analysis. The results of this study shed light on how language shapes online interactions and further our knowledge of cross-cultural communication in the digital era.